Effect of temperature and thermal cycling on fatigue crack growth in aluminium reinforced with GLARE bonded crack retarders. (May 2017) - Syed, Abdul Khadar; Zhang, Xiang; Moffatt, James E.; Fitzpatrick, Michael E.
Highlights: GLARE straps provided considerable reduction to FCG rate at RT. At −60 °C, baseline FCG life is more than tripled owing to the reduced FCG rate. At 70 °C, baseline FCG life is shorter owing to greater stress intensity factors. Thermal cycling does not impair the performance of BCR tested at RT. Abstract: This paper presents results of fatigue crack growth testing of aluminium alloy 2624-T351 reinforced by bonded crack retarders made of GLARE fibre-metal laminate. Specimens were tested at room temperature, 70 °C and −60 °C. Better performance of the crack retarders in terms of increased fatigue life was achieved at room temperature than at the two temperature extremes. This is attributed to a combined effect of change in the fatigue crack growth rate at temperature in the substrate material, and residual stress generated at temperatures above or below room temperature. The change in fatigue crack growth rate was measured, and the substrate deformation and the stress intensity factors at temperature were calculated by Finite Element Analysis. In addition, the effect of thermal cycling on fatigue crack growth rate was investigated by exposing the specimens to repeated thermal cycles between 70 °C and −60 °C prior to fatigue testing. It is concluded that the pre-test thermal cycling has little effect on the fatigue crack growth rate.